Embodied Ethos and a Pedagogy of Presence: Reflections from a Writing Yogi - Christy I. Wenger (Journal of the Assembly for Expanded Perspectives on Learning, 2018)
Students reflect on how practicing yoga affects their understanding of how they compose and how they represent themselves to others as they compose.